The Role of Al-Quran Hadith Teachers in Improving Al-Quran Reading at MTs Darun Nahwi Singajaya - Hafaf Fadilah; Syifa Nurfadilah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study is a qualitative study. The purpose of this study is to explain the level of students in reading the Qur'an. Describe the constraints in improving the ability to read the Qur'an, explain the strategies of Al-Qur'an Hadith teachers in the level of Qur'an reading skills, and increase the role of Al-Qur'an Hadith teachers in improving the ability to read the Qur'an by MTs Darun Nahwi students. The results of this study are 1) based on this test by the researcher, it shows that of all MTs Darun Nahwi students there are still some students who cannot read the Qur'an but other students have the ability to read the Qur'an. 2) The constraints for the progress of reading the Qur'an are that there are still many students who have difficulty reading the Qur'an and the rules of reading it, and the attention of parents at home is lacking in advancing their children's skills.